Whether Tectono-Magmatic Regimes offer any Prospects for Primary Uranium Mineralization in Northern Pakistan - Tahirkheli, R. A. Khan; Kamal, Muhammad (Journal of Himalayan Earth Sciences, 1981)
The northern segment of Pakistan inhabits some of the loftiest mountain systems of the world. Nearly forty per cent of the rocks covering the surface area in this terrain are igneous, out of which over seventy per cent belong to the acid igneous domain. The Late Mesozoic - Cenozoic orogenic events had brought into being some of the major lineaments which have regional dimensions. Magmatic emanations associated with these shears belong to several generations; some of them belonging to the late phases have indicated some metallic mineral associations. A few known primary uranium mineralizations in this region are associated with some of these magmatic episodes. This paper discusses the tectono-magmatic environment of the northern Pakistan and delineates the metallogenic zones under the context of plate tectonics- where favorable conditions may exist for finding primary uranium mineralization.